Not just a tomboy a trans masculine memoir - Baldwin, Caspar J. 1989- (Jessica Kingsley Publishers, 2019)
This is the story of one trans man's exploration of gender identity, set against changing cultural attitudes from the 90s to the present day. Caspar Baldwin grew up in a time when being trans was not widely accepted by society, and though progress has been made since then, trans men are still underrepresented and misunderstood. Grappling with the messy realities of gender expectations while giving a stark and moving account of his own experiences, Baldwin grants a nuanced understanding of what it's like to be a trans boy or man. With its unflinching portrayal of the vulnerability, confusion, dysphoria, empowerment, peace and joy that are all part of the transition process, this provides an invaluable support for trans men and is a memoir that breaks the mould"--